Lightpath routing for intelligent optical networks. - Zhensheng Zhang (IEEE Network : the magazine of global information exchange)
An overview of current issues and challenges in lightpath routing for optical networks is given. An architecture is presented in which optical switches are deployed, usually in the core, to interconnect IP routers at the edges. Lightpath routing within this architecture follows the framework of generalized multiprotocol label switching. Our discussion pays particular attention to the aspects of optical routing that differ from routing in irrational IP networks. Such aspects include physical layer constraints, wavelength continuity, the decoupling of the control network topology from the data network topology, explicit routing with wavelength assignment, and diversity routing for fast protection. We also present an algorithmic framework for lightpath computation, highlighting the issue of wavelength continuity and the differences between lightpath computation and traditional IP route computation